Impact of Glucose Metabolism Disorders on IGF-1 Levels in Patients with Acromegaly - Dogansen, Sema Ciftci; Yalin, Gulsah Yenidunya; Tanrikulu, Seher; Yarman, Sema (Hormone and Metabolic Research, 2018)
In this study, we aimed to evaluate the presence of glucose metabolism abnormalities and their impact on IGF-1 levels in patients with acromegaly. Ninety-three patients with acromegaly (n=93; 52 males/41 females) were included in this study. Patients were separated into three groups such as; normal glucose tolerance (n=23, 25%), prediabetes (n=38, 41%), and diabetes mellitus (n=32, 34%). Insulin resistance was calculated with homeostasis model assessment (HOMA). HOMA-IR > 2.5 or ≤2.5 were defined as insulin resistant or noninsulin resistant groups, respectively. Groups were compared in terms of factors that may be associated with glucose metabolism abnormalities. IGF-1% ULN (upper limit of normal)/GH ratios were used to evaluate the impact of glucose metabolism abnormalities on IGF-1 levels. Patients with diabetes mellitus were significantly older with an increased frequency of hypertension (p<0.001, p=0.01, respectively). IGF-1% ULN/GH ratio was significantly lower in prediabetes group than in normal glucose tolerance group (p=0.04). Similarly IGF-1% ULN/GH ratio was significantly lower in insulin resistant group than in noninsulin resistant group (p=0.04). Baseline and suppressed GH levels were significantly higher in insulin resistant group than in noninsulin resistant group (p=0.024, p<0.001, respectively). IGF-1% ULN/GH ratio is a useful marker indicating glucose metabolism disorders and IGF-1 levels might be inappropriately lower in acromegalic patients with insulin resistance or prediabetes. We suggest that IGF-1 levels should be re-evaluated after the improvement of insulin resistance or glycemic regulation for the successful management of patients with acromegaly.
Keywords: acromegaly; insulin resistance; prediabetes; diabetes mellitus; IGF-1 levels; IGF-1/GH ratio